Legal Assistance For “Nyonya Umi Fried Onion” Enterprises Micro, Small And Medium Enterprises (MSMEs) In Dringu Village, Probolinggo Regency, East Java, Indonesia - Hervina Puspitosari; Gideon Setyo Budiwitjaksono; Vierenez Vaskhie Siahaan; Dhea Veranica Isabella (International Journal Of Community Service, 2023)
This research explores the crucial role of Micro, Small and Medium Enterprises (MSMEs) in Indonesia's economic development, especially in Probolinggo, East Java. MSMEs are identified as an effective measure in reducing poverty and unemployment, as well as a key element of economic recovery after the economic crisis. The government considers MSMEs as the largest group of economic actors in Indonesia, contributing significantly to national development. While Nyonya Umi's Fried Onion products have great potential to enter the market, challenges arise because they do not yet have brand rights, making development difficult and involving the risk of losing product assets to other parties. In this context, legal aid is considered essential to provide protection to the MSME Business Center in Dringu village, support its development, and overcome barriers such as the absence of a brand.